(untitled) - LIŠKA, Vladimír; VRÁBEĽ, Róbert (Trends in education, 2009)
Substitution method to multidimensional integrals is a powerful tool for calculating them, but its routine application can lead to lengthy calculations. This fact presents the example of three-dimensional integral, where the area of integration is cone with the axis of rotation ox .
Keywords: three-dimensional integral; Fubini's theorem; cylindrical coordinates.